Animal Models for the Study of Food Allergies. Issue 3 (23rd March 2023) - Kazemi, Sahar; Danisman, Ece; Epstein, Michelle M.
Abstract: In the last decades there has been a parallel increase in the incidence of food allergies and the development of experimental mouse models. These models have improved our understanding of the disease but do have limitations. For instance, they do not entirely reproduce human pathophysiology; moreover, validated and predictive models are absent. Nevertheless, the models provide opportunities to further understand fundamental disease mechanisms. The selection of any of the many experimental models depends on the research aims. This overview focuses on IgE‐mediated food allergy in wild‐type, genetically modified, and humanized mouse models and presents a comprehensive overview of the currently used protocols, challenges, and limitations, as well as provides guidelines for model selection based on the three critical areas of research: 1) safety assessment, 2) evaluating treatment, and 3) elucidating pathophysiology. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.